Republic of Serbia : 2017 Article IV Consultation, Seventh Review Under the Stand-by Arrangement and Modification of Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for the Republic of Serbia. (IMF Staff Country Reports; Country Report ;, 2017)
This 2017 Article IV Consultation highlights that Serbia's economy has strengthened impressively since the adoption of the economic program supported by the Stand-By Arrangement. Economic growth is expected to reach 3 percent in 2017. The fiscal deficit should narrow to 1.1 percent of GDP-the lowest level since 2005-and public debt is heading down faster than projected. Contrary to expectations, the larger than planned fiscal tightening has been associated with increased growth, reflecting the confidence engendered by decisively tackling the public debt sustainability concerns. Moreover, unemployment is falling sharply, along with the level of banks' nonperforming loans, while inflation has been maintained at low levels.